AtlantOS data products from multibeam EM122 data: Maria S. Merian cruise MSM59/2 Transit (South Atlantic and Indian Ocean) - Anne-Cathrin Wölfl; Benjamin Wheeler (PANGAEA, 2018)
The multibeam raw data has been cleaned, quality assured and processed using QPS Qimera. Data products include ungridded soundings, bathymetric grids (100 m resolution) and an area shapefile. The data processing and provision took place within the EU Horizon 2020 project AtlantOS - Optimising and Enhancing the Integrated Atlantic Ocean Observing Systems.